2020
DOI: 10.3390/photonics7040127
|View full text |Cite
|
Sign up to set email alerts
|

Programmable High-Resolution Spectral Processor in C-band Enabled by Low-Cost Compact Light Paths

Abstract: The flexible photonics spectral processor (PSP) is an indispensable element for elastic optical transmission networks that adopt wavelength division multiplexing (WDM) technology. The resolution and system cost are two vital metrics when developing a PSP. In this paper, a high-resolution 1 × 6 programmable PSP is investigated and experimentally demonstrated by using low-cost compact spatial light paths, which is enabled by a 2 K (1080p) liquid crystal on silicon (LCoS) and two cascaded transmission gratings wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Z. Liu et al demonstrated a high-resolution 1 × 6 programmable photonics spectral processor (PSP) using low-cost, compact spatial light paths. This processor allows independent manipulation of filtering bandwidth and power attenuation for each wavelength channel, offering potential benefits for WDM systems [10].…”
mentioning
confidence: 99%
“…Z. Liu et al demonstrated a high-resolution 1 × 6 programmable photonics spectral processor (PSP) using low-cost, compact spatial light paths. This processor allows independent manipulation of filtering bandwidth and power attenuation for each wavelength channel, offering potential benefits for WDM systems [10].…”
mentioning
confidence: 99%